Development of whey milk drink - N. S. Bezverkhaya; О. A. Ogneva (Новые технологии)
At present in the Russian Federation fortified food products have gained extensive promotion as the newest and promising direction in the food industry. Almost every dairy processing enterprise has a line of fortified products in its product range. Vitamins, antioxidants, vitamin-like substances, flavoring components, micro and macro elements, phospholipids, prebiotics, probiotics, essential amino acids, polyunsaturated fatty acids can be used as enriching ingredients. On the other hand, the problem of targeted and economically profitable use of secondary milk processing resources is a significant problem. Production of cottage cheese, cheese and casein produces a liquid by-product, which is one of the largest additional sources of dietary protein and lactose as an important source of carbohydrates. The aim of the research is to develop whey fermented milk drink. The objectives of the research are to determine the effect of Jerusalem artichoke syrup on the organoleptic characteristics of the developed fermented milk drink; to optimize empirically the recipe composition of the developed fermented milk drink; to select experimentally the species composition of the starter micro flora of the developed fermented milk drink. The objects of the research are milk serum, Jerusalem artichoke syrup, ground ginger and cinnamon, starter culture on pure cultures of lactic acid microorganisms consisting of Str. thermophilus strains, viscous strains and Lbm. Bulgaricus and B. bifidum 791 in a ratio of 2:1:1. It can be concluded that the use of flavored fillers in the technology of whey fermented milk drink makes it possible to obtain a new product with competitive characteristics.